The Mycobacterium tuberculosis membrane protein Rv2560 - Biochemical and functional studies (2007)
The characterization of membrane proteins having no identified function in Mycobacterium tuberculosis is important for a better understanding of the biology of this pathogen. In this work, the biological activity of the Rv2560 protein was characterized and evaluated. Primers used in PCR and RT-PCR assays revealed that the gene encoding protein Rv2560 is present in M. tuberculosis complex strains, but transcribed in only some of them. Sera obtained from rabbits inoculated with polymer peptides from this protein recognized a 33 kDa band in the M. tuberculosis lysate and a membrane fraction corresponding to the predicted molecular mass (33.1 kDa) of this protein. Immunoelectron microscopy analysis found this protein on the mycobacterial membrane. Sixteen peptides covering its entire length were chemically synthesized and tested for their ability to bind to A549 and U937 cells. Peptide 11024 (121VVALSDRATTAYTNTSGVSS140) showed high specific binding to both cell types (dissociation constants of 380 and 800 nm, respectively, and positive receptor-ligand interaction cooperativity), whereas peptide 11033 (284LIGIPVAALIHVYTYRKLSGG304) displayed high binding activity to A549 cells only. Cross-linking assays showed the specific binding of peptide 11024 to a 54 kDa membrane protein on U937. Invasion inhibition assays, in the presence of shared high-activity binding peptide identified for U937 and A549 cells, presented maximum inhibition percentages of 50.53% and 58.27%, respectively. Our work highlights the relevance of the Rv2560 protein in the M. tuberculosis invasion process of monocytes and epithelial cells, and represents a fundamental step in the rational selection of new antigens to be included as components in a multiepitope, subunit-based, chemically synthesized, antituberculosis vaccine. © 2007 The Authors.